2022
DOI: 10.1113/jp283698
|View full text |Cite
|
Sign up to set email alerts
|

Common synaptic input, synergies and size principle: Control of spinal motor neurons for movement generation

Abstract: Understanding how movement is controlled by the CNS remains a major challenge, with ongoing debate about basic features underlying this control. In current established views, the concepts of motor neuron recruitment order, common synaptic input to motor neurons and muscle synergies are usually addressed separately and therefore seen as independent features of motor control. In this review, we analyse the body of literature in a broader perspective and we identify a unified approach to explain apparently diverg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 54 publications
2
52
0
Order By: Relevance
“…The foundation of this work relies on the concept of modularity of movement control (5, 6, 8), and the necessary transmission of common inputs to motor neurons to generate and modulate muscle forces (10, 25, 39, 40). We recently proposed that the central nervous system coordinates the firing activity of hundreds of spinal motor neurons during movements by transmitting a few correlated inputs to subgroups of these motor neurons (25). These ‘clusters’ can span over several muscles (14, 15, 23), and multiple common inputs can reach a single muscle or a part of it (14, 20, 21, 22, 23, 24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The foundation of this work relies on the concept of modularity of movement control (5, 6, 8), and the necessary transmission of common inputs to motor neurons to generate and modulate muscle forces (10, 25, 39, 40). We recently proposed that the central nervous system coordinates the firing activity of hundreds of spinal motor neurons during movements by transmitting a few correlated inputs to subgroups of these motor neurons (25). These ‘clusters’ can span over several muscles (14, 15, 23), and multiple common inputs can reach a single muscle or a part of it (14, 20, 21, 22, 23, 24).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been observed that a pool of motor neurons innervating the same muscle do not always receive the same inputs (14, 20, 21, 22, 23, 24). Therefore, we recently proposed that the central nervous system may generate a movement by transmitting a few inputs to groups of motor units (25), rather than to entire pools innervating individual muscles. In this view, the study of human movement control should be done at the motor neuron level, using methods that can identify the structure of the common inputs transmitted to motor neurons, rather than at the global muscle level.…”
Section: Introductionmentioning
confidence: 99%
“…For example, motor neurons innervating type II muscle fibers in general have larger somas and more dendrites as well as a larger axonal diameter sizes, the latter enabling faster conductance velocity ( 306 , 319 ). The physical dimensions of the motor neuron somas contribute to the determination of the recruitment threshold ( 320 ). Thus, the larger surface area and high number of ion channels in fast motor neurons result in a lower input resistance compared with the small surface area with fewer ion channels of slow motor neurons ( 320 ).…”
Section: Physiological and Cellular Adaptation To Exercise Training: ...mentioning
confidence: 99%
“…The physical dimensions of the motor neuron somas contribute to the determination of the recruitment threshold ( 320 ). Thus, the larger surface area and high number of ion channels in fast motor neurons result in a lower input resistance compared with the small surface area with fewer ion channels of slow motor neurons ( 320 ). According to Ohm’s law ( V = I × R ), the same synaptic input thus induces greater changes in the membrane potential of small motor neurons (with a higher resistance) compared with large motor neurons (with a lower resistance).…”
Section: Physiological and Cellular Adaptation To Exercise Training: ...mentioning
confidence: 99%
“…Studies in recent years have investigated muscle synergies by focusing on frequency-domain crosscoherence among muscles, leading to important findings about inter-muscular coordination and the underlying mechanisms of motor control, establishing solid foundations for the field [9][10][11][12][13][14][15][16][17][18][19] , muscle synergy approaches inherently constrain the dimensionality of the neural control to be less than or equal to the number of recorded muscles, and rely on the assumption that all motor neurons from a motor pool (i.e., ensemble of motor neurons innervating a muscle) rigidly receive the same inputs 20 .…”
Section: Introductionmentioning
confidence: 99%